Child Care Services for Three to Six Years Old Children in Urban Anganwadi’s in Kozhikode Corporation in Kerala –An Evaluation Study - Sivakumar D; Bina, Thomas; Deepika (National Journal of Community Medicine, 2015)
Introduction: Integrated Child Development Services is the largest national programme for the development of mothers and children in the world. The services are rendered through Anganwadi worker (AWW) at Anganwadi centre (AWC). An evaluation study is carried out to assess the services provided by the anganwadi cen- tres to 3 to 6 year old children in Urban ICDS blocks in Kozhikode Corporation to study the shortcomings in implementation, im- proving the services and in decision making of the programme. Methods: A cross sectional descriptive study was carried out in 4 urban ICDS blocks in Kozhikode. Data was collected using pre- tested semi structured questionnaire and by observation of an- ganwadi centres and records at the time of visit and interviewing anganwadi workers and anganwadi helpers. Results : Among 117 anganwadi centres, 73(62.4%) of AWC’s pro- vided average services to 3 to 6 year old children , only 26(22.2%) of centres provided good services and 18 (15.4%) of AWC’s with poor performance needs to be targeted for improvement . Conclusions: There is a need for effective coordination between the health functionaries and the anganwadi workers in immunisa- tion, growth monitoring, health checkups and referral services, nu- trition and health education.